Persepsi Guru Madrasah Ibtidaiyah Terhadap Penggunaan Media Digital dalam Proses Pembelajaran - Sudarsih, Lilis (Universitas Islam Zainul Hasan Genggong, 2025)
. This study aims to analyze Madrasah Ibtidaiyah teachers' perceptions of the use of digital media in the learning process. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and document analysis. The research subjects involved teachers from several Madrasah Ibtidaiyah in a particular area. The results show that the majority of teachers have a positive view of the use of digital media, as it is considered capable of increasing student engagement, enriching learning materials, and supporting the effectiveness of the teaching-learning process. However, the study also found challenges, such as limited technological infrastructure, lack of training, and barriers to adaptation to new technologies. These findings provide important implications for education policy development, particularly in the provision of technology facilities and adequate training for teachers. This study recommends strengthening institutional support to optimize the integration of digital media in education at the Madrasah Ibtidaiyah level.